AN ANALYSIS OF STIKES FLORA NURSING STUDENT’S DIFFICULTY IN ANSWERING TOEFL QUESTIONS - Susiana Kaban; Rina Rahmadani Sidabutar (Institut Pendidikan Tapanuli Selatan, 2020)
English is an important competency for nursing workers in this industrial era 4.0, the high demand for Indonesian nurses from abroad is not fulfilled because of the low English skill. The standard of English proficiency is generally measured by the TOEFL test. The purpose of this study was to determine the difficulties faced by seventh semester nursing students of Ners Department of STIKes Flora in answering TOEFL questions and to describe the study habits of students who have high TOEFL scores and students who have low TOEFL scores. The subjects of this study were 15 seventh semester students of Ners Department of STIKes Flora. The research location was at STIKes Flora. This is a descriptive qualitative research in which data were obtained using (1) documentation method (2) interview method to analyze student difficulties in answering TOEFL questions (2) questionnaire method to find out the description of English learning habits and the data were analyzed using descriptive analysis techniques. From the results of the study it was found that the students’ difficulties in answering TOEFL questions were the lack of knowledge and English skill, difficulty in managing time, and problem with memory due to lack of preparation for the TOEFL exam, while the study habits of students with high TOEFL scores had better performance than with the study habits of students with low TOEFL scores.